Predictors of parenting dimensions in families of children with disabilities - Vrankić Pavon, Marijana; Žic Ralić, Anamarija (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Raising a child with disability presents distinctive challenges, with parental behaviors influenced by various factors. Understanding these factors is crucial, as parental behaviors significantly influence a child’s development and adjustment. Aim. This study aims to investigate the predictors of parental behavior among parents of children with disabilities and parents of typically developing children, focusing on sociodemographic variables of both parents and children, and specific characteristics related to children with disabilities. Methods. The study involved 315 parents of children with disabilities and 552 parents of typically developing children in Croatia, with data collected via online questionnaires on sociodemographic variables, parenting behavior, child disability type, independence, and challenging behaviors. Mann-Whitney U tests and hierarchical regression analyses were used. Results. Results indicate no significant differences in parental support, restrictive control, or permissiveness between the groups. However, parents of children with disabilities adjust parenting to their child’s disability, challenging behaviors, and self-care needs. Conclusion. Parents of children with disabilities adapt their parenting based on the nature of their child’s disability, as well as the level of support a child needs. Recognizing these dynamics can guide the development of support strategies for families, highlighting the importance of personalized interventions to address specific challenges faced by parents raising children with disabilities.
Keywords: parenting behaviors; children with disabilities; self-care; challenging behaviors; support strategies